For brown girls with sharp edges and tender hearts : a love letter to women of color - Mojica Rodríguez, Prisca Dorcas, 1985- (Seal Press, 2021)
"For generations, women of color have had to push against powerful forces of sexism, racism, and classism in this country, and too often, they have felt that they had to face these challenges alone. Through her writing, her activism, and through founding Latina Rebels, Prisca Dorcas Mojica Rodríguez fought to create community to help women fight together. Now her new book For Brown Girls with Sharp Edges and Tender Hearts offers wisdom and a liberating path forward for all fellow Brown girls. Her new book addresses a range of issues: How can Brown girls survive, and thrive, in spaces that were never meant for us? How do we feel pride when we're forced to code-switch? How can we deal with our own imposter syndrome? How do we free ourselves from internalized racism, when it comes to colorism within our communities? And what does it mean to decolonize our worldview? Chapter by chapter, Mojica Rodríguez not only defines these terms, she crafts powerful new ways to address these challenges. She defies "universal" white narratives by telling her own stories. She gives readers access to the knowledge that changed her life and powered her activism. Too often Brown girls have had to strive and climb and force themselves into predominantly white spaces that were never built for them. Here Mojica Rodríguez crafts a love letter and a manifesto to Brown girls, guiding them toward women who have innovated a sense of pride and sisterhood when the dominant community has failed them. In the end, this timely and urgent book energizes a movement with essential tools to help women speak up and make change. May it spark a fire within you"--